Study of Vitamin-B1 Interaction with Dihydroxyanthraquinone Dye and its Thermodynamic Elucidation - Khorsandi, Khatereh; Hosseinzadeh, Reza; Gheshlagi, Mohammad (Journal of Applied Solution Chemistry and Modeling, 2013)
Interaction of Alizarin Red-S dye with thiamin (vitaminB1) was studied using spectrophotometric method at room temperature and neutral pH. The yellowish color appeared due to the Alizarin Red-S interaction with vitamin B1. According to the Benesi-Hildebrand equation, the related equilibrium constant, Kb, for the interaction has been determined and the Gibbs free energy of interaction has been calculated. Also the Benesi-Hildebrand equation has been used for assay of vitamin B1 in tablets. Results show that the method has good sensitivity for vitamin B1 and is in good agreement with HPLC method.